Peningkatan Hasil Belajar Siswa Dengan Model Pembelajaran Think Pair Share (TPS) Dengan Media KWARBI - Sari, Dewi Indah (SCAD Independent, 2024)
The use of KWARBI media in learning can be integrated effectively into Think Pair Share (TPS) cooperative learning activities by modifying it into an engaging educational game. The TPS learning model supported by KWARBI media serves as an implementation of the 2013 Curriculum, which emphasizes scientific, student-centered, and activity-based learning processes. This study employed Classroom Action Research (PTK) consisting of two cycles with the primary objective of determining the extent to which the use of the TPS model assisted by KWARBI media can improve students’ biology learning outcomes. During the learning process, KWARBI media was utilized both in discussion sessions and during evaluation activities. Its visual and verbal elements help students strengthen memory retention, making the learning experience more meaningful and long-lasting. The TPS model combined with KWARBI media also reflects the principles of PAIKEM (Active, Innovative, Creative, Effective, and Enjoyable Learning), as it encourages students to think individually, collaborate in pairs, and communicate findings in groups. The results of this study showed that students’ learning outcomes on Plantae and Animalia topics significantly improved after the implementation of this learning approach in class X-Acceleration of SMA Negeri 1 Malang during the 2013–2014 academic year. Furthermore, the TPS strategy assisted by KWARBI media has the potential to be applied to other basic competencies or topics that possess conceptual characteristics similar to Plantae and Animalia. KWARBI media can also be developed by students as a creative assignment for materials that have not yet been prepared by the teacher, thus increasing student engagement and fostering independent learning skills.